Optimization Making Glucosamine Hydrochloride (HCl GlcN) of Crab Shell Waste through Chemical Hydrolysis - Alfiana Nurjannah; Darmanto Darmanto; Ima Wijayanti (Jurnal Pengolahan Hasil Perikanan Indonesia, 2016)
Processing of glucosamine from crab shell chitin can be done by chemical hydrolysis with hydrochloricacid (HCl). The purpose of this research was to determine the effect of chitin immersion by variousconcentrations of HCL toward glucosamine generated and the selected concentration of HCL to glucosaminechemical hydrolysis process. The material used in this study is crab shells from Betahwalang village, Demak,and the solvent is HCl and NaOH. Parameters are glucosamine yield, melting point, loss on drying (LoD),PH and spectrum analysis with FTIR method. Research using experimental design completely randomizeddesign three times treatment with repetition. The results were analyzed using analysis of variance (ANOVA)to determine the differences between treatments concentration of 27%, 32% and 37%. The selected weretested with honestly significant difference test. The results showed differences in the concentration of HClused cause differences in the characteristics of the resulting glucosamine. The higher HCl concentrationsused, the lower the rendemen results and melting point. The selected HCL treatment concentration was at27% observed from glucosamine yield (18.39%) and the melting point (192-195oC). The treatment of 37%produces LoD (0.647%), pH (4.01) and spectrum glucosamine is an O-H group (3297.75/cm), the group ofN-H (1617.53/cm), the group of C-N (1394.94/cm).Keywords: crab shells, chitin, melting point, glucosamine